Software applications : concepts, methodologies, tools, and applications - Tiako, Pierre F. (Hershey, PA : Information Science Reference, 2009)
'This set of books contains a comprehensive collection of over 300 authoritative contributions from top influential experts in the field of software applications'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Computer software; Software engineering